Study of Corrosion in a Biomass Boiler. (27th March 2013) - Berlanga, C.; Ruiz, J. A.
Abstract : Biomass plants, apart from producing energy, help to reduce CO2 (g) emissions. One of the biggest problems for their development is superheater corrosion due to fuel corrosivity, especially of the straw. This limits both the temperature of the vapour and also the effectiveness of the plant. In order to know more about the reactions which happen inside the boiler of biomass, thermodynamic calculations using software (HSC Chemistry) have been carried out. Field tests have been carried out in the Sangüesa Biomass Plant in Navarra (Spain): determination of the types of oxides and the deposits formed on the superheaters tubes as well as a program to measure temperatures. Finally, the global results are discussed.